Reconnecting to others: grounded theory of social functioning following age-related hearing loss. Issue 9 (29th September 2022) - Fowler, Elizabeth; Woodside, Jayne V.; Kee, Frank; Loughrey, David; Lawlor, Brian; McHugh Power, Joanna
Abstract: Age-related hearing loss (ARHL) is common and a known risk factor for social disengagement in later life. This study explored social functioning following a diagnosis of ARHL. Using a constructivist grounded theory approach we developed an interview schedule to advance a grounded theory from data collected from six older adults who used either hearing aids or cochlear implants. Interview questions concerned social functioning as well as focusing on their perspective of the impact of ARHL on cognitive functioning. We describe a grounded theory conceived as 'Reconnecting to Others'. This theory posits that participants faced social challenges in relation to their ARHL, and resolved these challenges partly through the use of hearing aids and cochlear implantation. The theory also emphasises the importance of help from other hearing aid users for new users, and corroborates prior findings about strategies older adults with ARHL use to cope with their hearing impairment in various social situations. Once hearing aids and cochlear implants are used and adapted to with the help of peers, participants completed their journey by helping others who had received diagnoses of ARHL. Additionally, participants spoke of the pleasure of hearing again. Interestingly, no participant felt that their ARHL had impacted their cognitive functioning. Our theory provides a basis for explaining existing quantitative findings as well as creating new hypotheses for future testing.